Analisis makna metaforis dalam terjemahan lirik album The Tortured Poets Department: The Anthology di Spotify - Niko Dwi Kuncoro (Sintesis, 2025)
This study examines how translation strategies influence metaphorical meaning in the Indonesian translation of Taylor Swift’s lyrics from The Tortured Poets Department: The Anthology on Spotify and identifies the dominant type of equivalence applied. Using a descriptive qualitative method, six songs were selected for their metaphorical expressions and cultural references. Data were collected through listening and note-taking, then analyzed using George Lakoff and Mark Johnson’s conceptual metaphor theory and Eugene Nida’s equivalence theory. The analysis identified 18 conceptual metaphors, consisting of 8 ontological, 7 orientational, and 3 structural. In terms of translation strategies, dynamic equivalence appeared in 15 cases, while formal equivalence occurred in 3. The findings show that ontological and orientational metaphors are the most frequent, while dynamic equivalence dominates in maintaining emotional and cultural nuances, particularly in chorus sections. These results suggest that dynamic strategies are more effective in preserving the poetic and emotional essence of metaphor-rich lyrics. They also highlight the importance of adopting flexible and culturally sensitive approaches in lyric translation, especially in the context of globalized music platforms like Spotify.